Theo van Baaren’s Systematic Science of Religion Revisited: The Current Crisis in Dutch Study of Religion and a Way Out - Davidsen, Markus Altena (NTT, 2020)
This article revisits Theo van Baaren’s (1912-1989) call for a ‘systematic science of religion’. With this call Van Baaren urged Dutch scholars of religion to do away with the religionist biases of the phenomenology of religion, while retaining comparison as a cornerstone of the discipline. Unfortunately, Van Baaren’s programme was never realized in the Netherlands, and Dutch study of religion became dominated instead by a particularist paradigm that, while producing eminent studies of individual religions, lacked an interest in theorizing religion in general. Deprived of a common object and aim, Dutch scholarship on religion has become fragmented, and Dutch scholars of religion have been in no good position to fend for themselves in face of institutional restructurings, budget cuts, and general hostility towards the humanities. With an eye to the Nordic countries I propose a reorientation towards a systematic science of religion à la Van Baaren as a way out of the academic and institutional crisis.